A TAXONOMIC STUDY OF THE GENUS TRIBULUS L. IN EGYPT I- MORPHOLOGICAL FEATURES - Kadria Ahmed; Amaal Mohamed (Arab Universities Journal of Agricultural Sciences, 2005)
This work aims at classifying the genus Tribulus which is represented in Egypt by 7 taxa (6 species & one variety) viz.: Tribulus terrestris, T.terrestris var. bicornu-tus, T.pentandrus, T.macropterus, T.megistopterus, T.mollis and T.kaiseri according to the current classical morphological features including those of flower which can lead to a correct taxonomic decision. The work includes detailed comparative vege-tative and reproductive morphology of the studied taxa, while drawings representing the extracted results are tried into cumulative plates. Also an artificial indented di-chotomous key for the studied taxa is constructed. The key easily differentiated the pentacyclic flowered taxa from the tetracyclic in 2 separated collections. The 1st is composed of 5 taxa in which; nature of pericarp (bony or herbaceous), leaflet pairs into large leaf (7 or 6), calyx (persistant or deciduous), anther connection (basi-or dorsifixed) and others are found effective in identification. On the other hand; calyx imbrication (quincuncial or ascending) and stigma (persistant or deciduous) are used in separating the 2 spp. within the 2nd collection.